Operating personnel safety during the administration of Hyperthermic Intraperitoneal Chemotherapy (HIPEC). (September 2016) - Kyriazanos, Ioannis; Kalles, Vasileios; Stefanopoulos, Anastasios; Spiliotis, John; Mohamed, Faheez
Abstract: Cytoreductive surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) is increasingly used in the treatment of peritoneal malignancies. The administration of HIPEC after complete cytoreduction offers the combination of the pharmacokinetic advantages inherent to the intraperitoneal delivery of cytotoxic chemotherapy, with the direct cytotoxic effects of hyperthermia, and has been reported to offer significantly improved patient outcomes. As a result, this novel method disseminates rapidly, with many surgical teams having developed peritoneal malignancy treatment programs. Protocols are needed for the introduction, handling, and management of chemotherapeutic agents in the operating room to minimize risk to the staff involved in the procedure. The personnel exposure during CRS and HIPEC may arise from different routes, such as air contamination, direct contact, manipulation of perfusates or chemotherapy solutions, and manipulation of objects/tissues exposed to chemotherapeutics. Guidelines for safe administration of HIPEC including environmental contamination risk management, personal protective equipment, and occupational health issues are yet to be established. This review summarizes the existing evidence regarding the safety considerations of HIPEC administration. Highlights: HIPEC is being increasingly used in the treatment of peritoneal surface malignancies. The handling of chemotherapeutic drugs in the OR may pose risks for the staff. Personnel exposure may arise from different routes. Current studies have failed to detect cytotoxic drug contamination. Adherence to safety guidelines minimizes the risk of personnel contamination.